Synthesis of partially fluorinated poly(arylene ether sulfone) multiblock copolymers bearing perfluorosulfonic functions. Issue 16 (23rd April 2015) - Assumma, Luca; Iojoiu, Cristina; Mercier, Régis; Lyonnard, Sandrine; Nguyen, Huu Dat; Planes, Emilie
ABSTRACT Partially fluorinated poly(arylene ether sulfone) multiblock copolymers bearing perfluorosulfonic functions (ps‐PES‐FPES), with ionic exchange capacity (IEC) ranging between 0.9 and 1.5 meq H+/g, are synthesized by regioselective bromination of partially fluorinated poly(arylene ether sulfone) multiblock copolymers (PES‐FPES), followed by Ullman coupling reaction with lithium 1, 1, 2, 2‐tetrafluoro‐2‐(1, 1, 2, 2‐tetrafluoro‐2‐iodoethoxy)ethanesulfonate. The PES‐FPES are prepared by aromatic nucleophilic substitution reaction by an original approach, that is, "one pot two reactions synthesis." The chemical structures of polymers are analyzed by 1H and 19F NMR spectroscopy. The resulted ionomers present two distinct glass transitions and α relaxations revealing phase separation between the hydrophilic and the hydrophobic domains. The phase separation is observed at much lower block lengths of ps‐PES‐FPES as compared with the literature. AFM and SANS observations supported the phase separation, the hydrophilic domains are well dispersed but the connectivity to each other depends on the ps‐PES block lengths. The thermomechanical behavior, the water up‐take, and the conductivity of the ps‐PES‐FPES membranes are compared with those of Nafion 117® and randomly functionalized polysulfone (ps‐PES). Conductivities close or higher to those of Nafion 117® are obtained. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 1941–1956